HUBUNGAN KOMPETENSI DAN DISIPLIN DENGAN KINERJA AWAK ARMADA KAPAL SUNGAI - Rudianto Rudianto; Adenan Suhalis; Yosi Pahala (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2014)
Performance and quality of the river fleet crew and productivity can be achieved if the crew has high discipline. Discipline is an aspect which contributes to decide things to be done in order to achieve certain goals.Continuous training indicates a level of responsibility to carry out the work in accordance with the abilities, skills and knowledge (initiative). A high discipline on a river flotilla crew will have a positive impact on performance. It means more training a river flotilla crew have more work can be completed and maintained. Based on the hypothesist, there is a significant positive relationship between the performance and competence of river fleet crew. It shows H1 is accepted. The second one, there is a significant positive relationship between the performance and discipline of river fleet crew, shown by H2 is accepted. The last one, there is a significant relationship between both competence and discipline and performance of river fleet crew that H3 is accepted.